Representasi Perempuan Bali Dalam Lirik Lagu Bu Darmi Karya Nostress - Dharmayanti, Ni Putu Gita; Gelgel, Ni Made Ras Amanda; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium, 2024)
The role of women on equality and gender relations is often raised as an object in the mass media, including the song lyrics. The description in the story are still in the subordinations and often creates stereotypes in the society. If this is not criticized it will be considered as natural and reasonable. In the future it can create a structure and system of gender injustice that is accepted and normalized as if nothing is wrong. The theme song of Bu Darmi is about women, especially Balinese women. This song tells about the life of the character bu Darmi, a Balinese woman who lives in an environment with thick culture and patriarchal system. In this song, Balinese women are described through two sides, there are in the private and public spheres. This study aims to explain the hidden meaning behind the song lyrics of Bu Darmi by Nosstress that have a corelations into the representation of women. This research using a qualitative approach with a Roland Barthes’s semiotic theory and representation theory from Stuart Hall, The results of this research signifies that Bu Darmi’s song describes the reality of the problems experienced by Balinese people related to patriarchal culture, women and the political ecology that occurs in Bali. Women conduct multidimensional and multigender plays as a women, labour, social society as well as arrange of several religious rituals.